Voltammetric Detection of Dopamine in Presence of Ascorbic Acid and Uric Acid at Poly (Xylenol Orange) Film-Coated Graphite Pencil Electrode - Umesh Chandra; B. E. Kumara Swamy; Ongera Gilbert; B. S. Sherigara (International Journal of Electrochemistry)
Poly (xylenol orange) film-coated graphite pencil electrode was fabricated for the detection of dopamine in the presence of ascorbic acid and uric acid in phosphate buffer solution of pH 7. The redox peaks obtained at modified electrode shows a good enhancement. The scan rate effect was found to be a diffusion-controlled electrode process. The electrochemical oxidation of dopamine was depended on pH, and the limit of detection was found to be 9.1 × 10−8 M. The simultaneous study gave and excellent result with great potential difference between dopamine and other bioactive organic molecules by using both cyclic voltammetric and differential pulse voltammetric techniques. The present modified graphite electrode was applied to the detection of dopamine in the injection samples, and the recovery obtained was satisfactory.